Ectopic Pregnancy: Incidence, Associated Risk Factors and Complications from Yashfeen Clinic - Enas Benaliwa,; Amel Morgham,; Nasreen Osman,; Faisal Ali,; Laila Almahdi,; Huda Othman,; Abdulhafid Abudher, (AlQalam Journal of Medical and Applied Sciences, 2022)
Aims. To explore the risk factors for ectopic pregnancy (EP) in women with planned pregnancy. Methods. This case series study, which included 147 women with planned pregnancy. In this group matched in terms of mother age, gestational age in weeks, Socio-demographic characteristics, reproductive history, gynecological history, contraceptive use, and history of infertility. Results. From147 patients diagnosed with EP, the age ranged between 22-49 years with mean age of 33.6 ± 4.2 years. Most patients who had ectopic pregnancy were multigravidas, multiparous, and those with previous history of abortion. 72.4 % of patients with ectopic pregnancy had a history of surgery (53.7% of the patients had previous C/S, 11.6% laparoscopy, 5.4% laparotomy, 3.4% E&C and 2% appendectomy). The result shows that the recurrence rate is 12.6% in those with previous ectopic and the most common site is the left fallopian tube pregnancy with a rate of 51.7%. Ninety-nine (67.3%) of the patients were treated by salpingectomy, 40 (27.2%) treated by salpingectomy. 143/147 (97.2%) of the ectopic pregnancy cases treated with laparoscopic surgical intervention successively and only four patients with scar ectopic pregnancy ended by laparotomy. Only 4.1% need a blood transfusion from all cases of ectopic pregnancies and no record of any maternal death. Conclusion. The signs and symptoms of EP can be similar to other complications of early pregnancy and the diagnosis often requires ẞ-hCG level and transvaginal ultrasonography. Once a diagnosis made, treatment options include medical therapy with methotrexate or surgery, which often managed laparoscopically. However, a delay in either diagnosis or treatment can lead to uterine rupture, hysterectomy, and significant maternal morbidity.